2021
DOI: 10.3389/fgene.2021.747581
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulated CLDN10 Predicts Favorable Prognosis and Correlates With Immune Infiltration in Gastric Cancer

Abstract: Background: CLDN10, an important component of the tight junctions of epithelial cells, plays a crucial role in a variety of tumors. The effect of CLDN10 expression in gastric cancer, however, has yet to be elucidated.Methods: Differential expression of CLDN10 at the mRNA and protein levels was evaluated using Oncomine, ULCAN, HPA and TIMER2.0 databases. Real-time polymerase chain reaction (RT-PCR) was utilized to further verify the expression of CLDN10 in vitro. Correlations between CLDN10 expression and clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…On the other hand, we found that IPS scores representing immune checkpoints were similarly inferior in the high-risk patients. Our findings were consistent with the previous studies (Liu et al, 2020;Rao et al, 2021), which indicate that PLPPS could guide the prognosis of GC patients. Different from the previous study focusing on the prognosis of GC, we further predicted sensitivity to chemotherapeutic agents in high-and low-risk group patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, we found that IPS scores representing immune checkpoints were similarly inferior in the high-risk patients. Our findings were consistent with the previous studies (Liu et al, 2020;Rao et al, 2021), which indicate that PLPPS could guide the prognosis of GC patients. Different from the previous study focusing on the prognosis of GC, we further predicted sensitivity to chemotherapeutic agents in high-and low-risk group patients.…”
Section: Discussionsupporting
confidence: 93%
“…We found that inflammation and immune response-related pathways were particularly scarce in high-risk patients. Interestingly, as reported by Rao et al (2021), "immune desert" tumors indicate adverse clinical outcomes. In addition, numerous studies indicate that high immune cell infiltration in GC patients was associated with a better long-term prognosis (Liu et al, 2020;Akshatha et al, 2021;.…”
Section: Discussionmentioning
confidence: 81%
“…CD39 + and CD39 + PD-1 + CD8 + T cells accumulate in the intestinal tissue during inflammation in CD, and the exhaustion of CD39-expressing CD8 + T cells is related to attenuation and remission of disease activity, which agrees with the report that TEX informs the clinical differences in adult onset IBD (147,148). Detailed roles of TEX in IBD deserve further With bioinformatics tools, researchers have identified multiple dysregulated molecules related to TEX and prognosis in GC or CRC tissues, such as CLDN10, C3AR1, ANTXR1, ANXA1, and PDPN (149)(150)(151)(152)(153). However, their exact regulatory mechanisms in T cell exhaustion remain for further validation and investigation.…”
Section: Colorectal Cancersupporting
confidence: 81%
“…With bioinformatics tools, researchers have identified multiple dysregulated molecules related to TEX and prognosis in GC or CRC tissues, such as CLDN10, C3AR1, ANTXR1, ANXA1, and PDPN ( 149 153 ). However, their exact regulatory mechanisms in T cell exhaustion remain for further validation and investigation.…”
Section: Tex In Gastrointestinal Cancermentioning
confidence: 99%
“…Claudins are the pivotal transmembrane proteins in TJs (tight junctions), and their expression are often reduced and play important roles in ccRCC, including CLDN8 (claudin-8) 11 , CLDN7 (claudin-7) 12 , and CLDN2 (claudin-2) 13 . Previous studies reported that CLDN10 (claudin-10), as a member of the claudins family, played a vital role in different tumors, including hepatocellular carcinoma 14 , papillary thyroid cancer 15 , and gastric cancer 16 . However, there are few studies on the roles of CLDN10 in kidney cancer.…”
Section: Introductionmentioning
confidence: 99%